Implementasi Media Pembelajaran Berbasis Teknologi Informasi Dalam Peningkatan Hasil Belajar Siswa Sekolah Menengah Pertama - Giat Prasetya (Universitas Muhammadiyah Surakarta, 2025)
This research aims to describe and analyze how teachers use/implement based learning media ofInformation Technology (IT) so that they can foster student responses and find out how teachersovercome obstacles in implementing based learning media of IT and find out the teacher evaluationsystem to determine learning outcomes by conducting observations and interviews with teachers atUPT SMPN 2 Ambarawa using observation sheets and interview guidelines. The results obtainedare that the use-based media of IT at UPT SMPN 2 Ambarawa is still limited, this is because thelimitations of teachers in the IT world are still lacking, besides the lack of facilities and infrastructurein schools, then the way teachers foster student responses varies, but with use-based learning mediaof IT can foster student responses. The teacher’s way overcome obstacles in based learning of IT isthat teachers more often use based learning media of IT that are easy to apply or operate based onthe abilities of teachers, students and existing facilities and infrastructure. Based on student learningevaluations, both formative and summative learning outcome evaluations from the cognitive, affectiveand psychomotor domains, based learning of IT has an effect on student learning outcomes, namelythat student learning outcomes increase compared to learning using monotonous or conventionalmethods. This can be seen from student scores that reach the KKM.